Armas, ropas, comidas y casernas. Vida cotidiana de un ingeniero militar en tiempo de guerra y prisión - Zozaya-Montes, Maria (2013)
The material conditions of elite prisoners, and the objects they saw and used in their common life at the beginning of the XIXth Century are not very well known, and we analyze them with the principal source of a prisoner´s diary written between 1809 and 1814.